2011
DOI: 10.3109/03639045.2011.613075
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physicochemical evaluation of a new tacrolimus tablet formulation for sublingual administration

Abstract: The aim of this study was to develop a new fast-disintegrating tablet formulation containing 1 mg tacrolimus for sublingual application. First, solid dispersions containing tacrolimus (2.5%, 5% and 10% w/w) incorporated in Ac-Di-Sol(®) and carriers (inulin 1.8 kDa and 4 kDa, and polyvinylpyrrolidone (PVP) K30) were prepared by freeze drying. Subsequently, a tablet formulation composed of a mixture of the solid dispersions, Ac-Di-Sol(®), mannitol, Avicel(®) PH-101 and sodium stearyl fumarate was optimized conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Properties of effective sublingually administered medications include high lipophilicity, small to moderate molecular weight, good solubility in salivary secretion, and favorable oil‐to‐water coefficients . Although tacrolimus is a larger molecule with erratic solubility, it is highly lipophilic with a favorable oil‐to‐water coefficient, making it an acceptable candidate for sublingual administration, and a novel sublingual‐specific formulation of tacrolimus was even reported in the literature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of effective sublingually administered medications include high lipophilicity, small to moderate molecular weight, good solubility in salivary secretion, and favorable oil‐to‐water coefficients . Although tacrolimus is a larger molecule with erratic solubility, it is highly lipophilic with a favorable oil‐to‐water coefficient, making it an acceptable candidate for sublingual administration, and a novel sublingual‐specific formulation of tacrolimus was even reported in the literature …”
Section: Discussionmentioning
confidence: 99%
“…15 Although tacrolimus is a larger molecule with erratic solubility, it is highly lipophilic with a favorable oil-to-water coefficient, making it an acceptable candidate for sublingual administration, and a novel sublingual-specific formulation of tacrolimus was even reported in the literature. 16 With regard to brand versus generic differences, the first generic formulation of tacrolimus capsules became available in August 2009. Although some in vitro studies found differences in rates of dissolution between the different generic formulations compared with the brand formulation, all studies included in this review used brand name Prograf (Astellas Pharma, Tokyo, Japan), limiting the applicability of study data to generic formulations.…”
Section: Discussionmentioning
confidence: 99%
“…It is not precluded, however, that repetitive and/or escalated dosing or other formulations of tacrolimus (e.g. intravenous solution or solid dispersions ) could result in significant drug exposure after sublingual exposure. This is in line with the finding that one in three subjects experienced local paraesthesia after sublingual dosing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the highly crystalline and poorly soluble characterizations of NFD result in lower oral bioavailability (Sawada et al, 2004). Application of solid dispersions composed of hydrophilic carrier in which a lipophilic drug is incorporated is a proven technique to improve the poor water solubility of drug (Huang et al, 2011;Srinarong et al, 2012). Furthermore, many studies have been reported that the solid dispersion technique was used to enhance oral bioavailability of poor water soluble drugs (Boghra et al, 2011;Tran et al, 2011).…”
Section: Preliminary Experimentsmentioning
confidence: 99%